2015
DOI: 10.5812/hepatmon.28315v2
|View full text |Cite
|
Sign up to set email alerts
|

Negative Association of Plasma Levels of Vitamin D and mir-378 With Viral Load in Patients With Chronic Hepatitis B Infection

Abstract: Background:Chronic Hepatitis B (CHB) is accompanied by inflammation of liver because of infection with Hepatitis B Virus (HBV). Previous studies revealed an inverse association between vitamin D and HBV DNA levels.Objectives:The current study aimed to investigate the levels of 25 (OH) D3 (the steady form of vitamin D), miR-378 and HBV DNA in the patients with CHB.Patients and Methods:One hundred and seventy three patients with HBeAg negative CHB were recruited for the study. Plasma levels of HBVDNA and 25 (OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…This is similar to Farnik et al (2013) who showed that 25 (OH) D levels were significantly lower in patients with HBV DNA levels (>2000 IU/ml). Also, Mohamadkhani et al, (2015) showed a significant inverse relationship between vitamin D levels and HBV replication in patients with chronic infection. Thus, it could be suggested that adequate levels of vitamin D may be one of the factors limiting HBV replication and reducing viral load in patients with OBI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to Farnik et al (2013) who showed that 25 (OH) D levels were significantly lower in patients with HBV DNA levels (>2000 IU/ml). Also, Mohamadkhani et al, (2015) showed a significant inverse relationship between vitamin D levels and HBV replication in patients with chronic infection. Thus, it could be suggested that adequate levels of vitamin D may be one of the factors limiting HBV replication and reducing viral load in patients with OBI.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it prevents viral entry into the host cell (Beard et al, 2011). Recently, Mohamadkhani et al, (2015) demonstrated that suppression of viral replication in patients with CHB infection may be mediated by vitamin D through increasing the expression of a unique miRNA ''miR-378''.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we made efforts to include some critical parameters, including levels of alanine transaminase (ALT), aspartate transaminase (AST), platelet count (PLT) and HBV DNA. Recently, Mohamadkhani et al 21. showed that there is a negative correlation between vitamin D3 levels and viral load in Iranian patients, with an acceptable population ( n = 173).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitation of HBsAg is considered as a prognostic and therapeutic biomarker in numerous studies. In addition, increasing levels of the reactive oxygen species (ROS) produced by granulocytes and macrophages related to the high titers of HBsAg are shown (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%